(3GdYbGFO GdYVOjIs - (3GdEjLj, CHh GdaVd, YVO GdOjf, YHO GdQMef Hf CMeO Hf YHO GdZaGQ, J (B756(3g`s ((3CMeO Hf eMjj GdOjf GdMSfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; hGdJUdjI GdMeO ddg Ydi fhGdg hGdUdGI Ydi fHjg eMeO hBdg bGd GdfHj Ydjg GdSdGe (B: " (3SJaJQb GeJj KdGKG hSHYjf (B( (3cPG (B) (3aQbI cdgG aj GdfGQ EdG hGMOI , bjd (B: (3hef ge ? bGd (B: (3GdPjf ge (B( (3cPG (B) (3Ydi eG GfG Ydjg hCUMGHj (B" (3hgPg YbGjO GdaQbI GdfGLjI hge GdCTGYQIs
(3BNQgG (B:s
(3hGdJhHI hGLHI hgj ebHhdI ef Gddg dWaG dG hLhHG hGdCeQ HGdeYQha JHY deG jDeQ Hg aEf cGf hGLHG ahGLH hEf cGf efOhHG aefOhH hTQWg Cf dG jDOj Edi GdaJfI hCf ojXf bHhdg hdG jLhR GdJLSjS KHJfG Gddg Ydi gPg GdYbGFO GdUMjMI hhabfG ddYed HeG jMH hjQVis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 295s
(3eYLe GdeDdajf (B2 / 76s
(3cTa GdXfhf (B2 / 1144s
(3TPQGJ GdPgH (B6 / 174s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds